Faktor determinan kepuasan kerja karyawan PT Sarana Scientifa Systemindo - Fanillah, Nesya; Farida, Farida (Sosio e-Kons, 2023)
In this statistical analysis, the researcher used the SPSS ver 25.0 For Windows program. Data processing was carried out with the SPSS (Statistical Package for The Social Science) ver 25.0programsm with a population of 50 employees. The technique for determining the sample in this study uses a saturated sampling technique or census sampling, in which all members of the population are sampled. Adjusted R Square with multiple determinations is 61.3% and the remaining 38.7% is the contribution of other factors. For multiple linear regression values, Y = 0.228 + 0.362 X1 + 0.258 X2 + 0.369 X3 and the F test = 5%. The F-count value is 26.826 and F-table is 2.81, meaning the F-count > F-table, it can be said that there is a significant influence between cultures. organization, leadership, and compensation for employee job satisfaction of PT Sarana Scientifa Systemindo